The Effectiveness Of Q And A Method On Critical Thinking Of Junior High School Female Students - Sadipour, Esmaeil; Hallajian, Mahdiye (The Turkish Online Journal of Design Art and Communication, 2016)
The main idea of this research was the study of educational effect of Q & A method on critical thinking of first grade female students. This was an experimental study in which multiple group patterns with pretest and posttest with control groupwas used. The population of this study consisted of the all first grade female high school students of a governmental school in area 2 of Tehran city. 1 high school was randomly selected between 35 high schools. This high school (Hoda) had 6 first grade classes and 195 students. Watson Glaser critical thinking questionnaire (1980) was performed on 195 students. 45 students who had 1 standard deviation below the average score were randomly divided into experimental and control groups. The results showed that Q & A method was effective on critical thinking of first grade high school students. In order to increase critical thinking of first grade high school students, teachers can use Q & A method.
Keywords: question and answer method; critical thinking; students and education; soru-cevap yöntemi; eleştirel düşünme; öğrenciler ve eğitim